COSMIC RADIATION EXPOSURE CALCULATIONS FOR INTERNATIONAL AND DOMESTIC FLIGHTS DEPARTS FROM ISTANBUL AND ANKARA. Issue 1 (10th December 2020) - Susam, L Amon; Alan, H Yilmaz; Yilmaz, A; Erol, A; Inci, C I; Akinci, F C; Akkus, B; Demir, M; Emirhan, M E; Faydasicok, O; Gudekli, E
Abstract: In this study, cosmic radiation doses were calculated for domestic and international flights departing from Istanbul and furthermore for domestic flights departing from Ankara using a software program called CARI-7A and also a mathematical method approach. Main parameters for calculating cosmic radiation are vertical cut-off rigidity, flight duration, latitude–longitude and altitude of the flight. Our calculation results agree with the measurements for domestic and international flights departing from Istanbul and Ankara.